Criminological Translators Are Used By The Law Enforcement Front Member Of The Islamic Foreign Front (Fpi) For Extra Judicial Killings, Which Refer To Murders That Occur Outside Of The Judicial Process (Analysis Of Supreme Court Decision Number 939 K/Pid - M. Luqmannul Hakim Siregar; Yasmirah Mandasari Saragih; Ismaidar, Ismaidar (CV. AFDIFAL MAJU BERKAH, 2024)
Regarding the use of firearms, Polri has special authority under Kapolri Regulation No. 1 of 2009 on the Use of Force in Police Action. One of the points presented in the Convention is that the use of force should be based on the principles of necessity, proportionality, general obligation, and reason. (reasonable). However, the realities on the ground just showed the number of incalculable uses of firearms over the past year. Several misarrests committed by the Polri, acts of torture, and extrajudicial killings using firearms were frequently carried out by the Polri. This writing uses descriptive legal research, and in this study, the author uses the normative research method of data collection. Library Research Criminal responsibility for the FPI Laskar shooting carried out by law enforcement without going through a legal process or a court ruling is a very serious and unlawful matter. Under Indonesian law, an independent and non-partisan court must ensure that everyone is tried fairly and openly. It can be concluded from this writing that the author's analysis of the sentencing of the gunman of a member of the Islamic Front Defender (FPI) (unlawful killing) in the Supreme Court decision No. 939 K/Pid/2022 is that the acts of the accused, M. Yusmin Ohorella, witness, and Elwira witness (deceased), are not a forced defense (noodweer) or excessive defense because the protection of the defendant is not in a life-threatening state